Floriculture as an Entrepreneurial Venture : Problems and Prospects - Todi, Ruchi (AMC Indian Journal of Entrepreneurship, 2021)
Floriculture, which is an ancient farming activity is the branch of horticulture that deals with the cultivation of flowers and ornamental plants. It is emerging as a profitable agri-business in India and worldwide in recent years. The government of India has recognized it as a â€˜Sunrise Industryâ€™ and also accorded it hundred percent export oriented status. Owing to the increasing demand for flowers for different purposes in the country, floriculture has become one of the most important commercial trades in some states of the country. The cultivation and sale of flowers is becoming a popular entrepreneurial venture in North-Eastern states also, especially in Assam but floriculture business in Assam is still in the infant stage. Floriculture entrepreneurs are facing several challenges which are hindering its growth and development. This research made an attempt to study the present status of floriculture business in India vis-Ã -vis that in the state of Assam. The study also attempted to find out the problems faced by the retail floriculture entrepreneurs as well as the flower cultivators of Kamrup district of Assam, which is regarded as the business hub of the North-Eastern region. It also highlights the prospects of floriculture business.